Efficacy and safety of pharmacotherapy for cancer cachexia: A systematic review and network meta‐analysis - Hao Chen; Masashi Ishihara; Hiroki Kazahari; Ryusuke Ochiai; Shigeru Tanzawa; Takeshi Honda; Yasuko Ichikawa; Nobuyuki Horita; Hisashi Nagai; Kiyotaka Watanabe; Nobuhiko Seki (Cancer Medicine)
Abstract Background Cancer cachexia affects more than half of all cancer patients, reducing survival rates. Evidence‐based approaches are urgently needed to optimize treatment. Methods A systematic review and network meta‐analysis were conducted to assess the effectiveness and safety of different pharmacotherapies for cancer cachexia. Three databases (PubMed, Cochrane Library, and Web of Science) were searched for the period from January 1, 2000, to March 20, 2024. The netmeta package in R software was used to calculate the pooled effect, employing a random effects model. Results Seven placebo‐controlled randomized trials involving 1421 patients were analyzed. Pairwise analysis showed that body weight increases were 4.6 kg (95% confidence interval [CI] 0.83–8.37 kg) for olanzapine, 3.82 kg (95% CI 0.73–6.91 kg) for espindolol (20 mg), 2.36 kg (95% CI 1.84–2.89 kg) for anamorelin (100 mg), and 1.31 kg (95% CI 0.42–2.19 kg) for anamorelin (50 mg). In terms of safety profiles, olanzapine demonstrated the lowest odds ratio when compared to placebo, at 0.26 (95% CI 0.07–0.94), followed by anamorelin (50 mg) at 0.86 (95% CI 0.30–2.48), and anamorelin (100 mg) at 0.89 (95% CI 0.42–1.88). However, network meta‐analysis could not confirm the superiority of olanzapine over anamorelin in terms of efficacy and safety. Conclusion Both olanzapine and anamorelin are useful in improving body weight in patients with cancer cachexia. Personalization may be helpful for different patients.